The Christie affair [large type] - Gramont, Nina de (Thorndike Press, a part of Gale, a Cengage Company, 2022)
"London, 1925. In a world of townhomes and tennis matches, socialites and shooting parties, Miss Nan O'Dea became Archie Christie's mistress, luring him away from his devoted and well-known wife, Agatha Christie. The question is, why? Why destroy another woman's marriage, why hatch a plot years in the making, and why murder? How was Nan O'Dea so intricately tied to those eleven mysterious days that Agatha Christie went missing?"--